Power dynamics, shifting roles, and learning: Exploring key actors in participation processes in the German energy transformation (Energiewende). (March 2022) - Ernst, Anna; Fuchs, Doris
Highlights: Key actors play crucial role and influence participatory decision-making clearly. Also, knowledgeable actors experience social learning and increase trust. Participation not always resolves conflicts but strengthen sense of community. Alternative solutions developed through participation may foster the Energiewende. Abstract: Scholars and practitioners generally see participation as a crucial element of governance strategies in pursuit of the goals of the German energy transformation. Research has focused on how to involve which groups of citizens in what kind of formats. The role of other "key actors", who organize, moderate, and participate as decision-makers or experts, has received much less attention. What functions do they fulfill and how do they influence the processes? How do they experience the processes and what does this experience imply for the ability of such processes to reach their transformative potential? This paper pursues these questions based on a survey with 148 key actors within the German Energiewende. It analyzes the range of tasks of key actors as well as their experience in terms of core social and cognitive dynamics in the participatory processes. We find that key actors can exercise a wide range of forms of influence, and that this influence is often further enhanced due to the multiple roles that individuals play. This aspect shows a risk that needs to be addressed: the potential lack of neutrality of particularly influential actors, tasked with organizing, moderating, mediating, and/or informing the participating citizens. Moreover, participation can prompt social learning among key actors, thereby underlining the potential contribution of participation to a sustainability transformation. Still, such learning does not provide a guarantee for conflict resolution.